Evaluation of desert aerosols impact on the solar radiation received by a photovoltaic field - ILBOUDO, Wend Dolean Arsène; KORGO, Bruno; Manga, Ngando Akoumou; BADO, Nébon; KIENO, Pèlèga Florent (European Journal of Applied Sciences, 2021)
This work focuses on the assessment of desert aerosols impact on the global solar radiation of photovoltaic (PV) solar fields. We used data from the experiment carried out using the multilayer model. Two parameters were used, namely the optical aerosol depth () and the aerosol deposition thickness on the surface of the PV solar field (X). By simulations, using variations of these parameters, we noted for the extremes values of (X = 1.5 μm, = 0 μm) and (X = 0, = 1.5 μm), an attenuation of the overall radiation of respectively 84.85% and 98.78%. This clearly shows that the parameter is the most attenuating factor of the global radiation in comparison with X. In view of the results obtained, it appears that desert aerosols have a significant impact on the electric yield of solar photovoltaic systems in West Africa especially in the Sahel region.